Pseudopapillary and Solid Tumor of Pancreas (PPSTP): Report of Seven Cases - Berkane, Salah (International Journal of Innovative Research in Medical Science, 2020)
Introduction: Described for the first time by Frantz in 1959 [1], pseudopapillary solid tumors of the pancreas (PPSTP) and have been defined since 1996 by the WHO as solids and papillaries [2]. They are particular by their clear predominance occurring in young women (30 years on average) and their good long-term prognosis [3]. Their positive diagnosis is often based on modern morphological examinations such as computed tomography and MRI. Surgery occupies a prominent place in their therapeutic management and all importance must be given to their diagnosis or at least their strong presumption in order to make curative surgical resection. We report seven cases all involve women, with an average age of 26.4 years (15-59 years). Radical surgery was performed in all cases with simple consequences in 5 patients and complicated in 2 others, including a pancreatic fistula and a pulmonary embolism. The histological study confirmed the diagnosis in all cases and the latter was supplemented by immunohistochemistry. In the long term, the seven patients are alive without recurrence at 100, 88, 78, 78, 74, 48 and 24 months. Conclusion: this form of pancreatic tumors has a good prognostic if well treated. The surgery is the best treatment. Clinician, radiologist, histologist and surgeon must know this disease.